The Mediating Effect of Employee well-being in relation to Role Stressors and Turnover Intention: A Conceptual Study - Naseebullah Langove; Ahmad Shahrul Nizam B. Isha; Muhammad Umair Javaid (International Review of Management and Marketing, 2016)
The technological revolution has escorted diverse roles with deleterious effects, which in turn triggers stress. Role stressors are comprehensively conceptualized as two distinctive variables, role conflict and role ambiguity. In literature, studies have shown a positive relationship of role conflict and role ambiguity with turnover intention while a negative relationship of employee well-being and turnover intention. However, very limited studies have attempted to examine the indirect effect of employee well-being between role stressors and turnover intention. The main objective of this conceptual study is to propose a framework whereby examining the relationship between role stressors and turnover intention with the mediating role of employee well-being. Simple random sampling will be used for data collection from IT executives of software companies of Malaysia in order to examine the relationship between role stressors, employee well-being and turnover intention with the help of Structure Equation Modeling (SEM). This study emphasizes the considerable importance of employee well-being interventions at the workplace to enhance the retention strategy.